Integrating Culture and Language Learning: Effects of Islamic Life Resource Pack (ILRP) on EFL Reading Comprehension in an Indonesian Islamic Junior High School - Sri Hidayati; Lasim Muzammil; Umiati Jawas (Journal of English Language Teaching and Linguistics, 2026)
Reading comprehension is a challenge for English as a Foreign Language (EFL) learners in Indonesian Islamic junior high schools. English texts can seem unrelated to students’ lives and values. The researchers evaluated the culturally responsive instructional resource, the Islamic Life Resource Pack (ILRP), to determine if students’ reading comprehension improved following the ILRP. The researchers conducted a pre-experimental, one-group pretest–posttest study of 26 eighth-grade students in an Islamic junior high school. The researchers conducted a pretest to assess reading comprehension, followed by ILRP-based instruction, and then did a posttest. The descriptive statistics and paired-samples t-test were used to analyze the findings. The researchers found a significant increase in reading comprehension after the intervention (M gain = 19.31, SD = 6.19; t(25) = 15.89, p < .001; 95% CI [16.81, 21.81]). This means that ILRP-based, culturally responsive reading instruction may help students to develop reading in Indonesian Islamic junior high schools. The findings should be taken with caution because they were conducted in a single intact group and sample size (n = 26), which may not allow us to draw strong causal conclusions due to possible threats to internal validity (e.g., testing effects and maturation). Despite these limitations, the study provides preliminary evidence to inform future larger-scale, controlled research on culturally responsive EFL reading instruction in Indonesian Islamic school settings.